Health professionals as parents are not immune to vaccine hesitancy – an Italian national survey. (13th November 2019) - Fonzo, M; Bertoncello, C; Cocchio, S; Zanovello, S; Bennici, S E; Baldovin, T; Buja, A; Napoletano, G; Russo, F; Baldo, V
Abstract: : Vaccine hesitancy is a growing concern in many European countries, including Italy, as instanced by alarming results from Eurobarometer 488 dated April 2019. In the view of the current magnitude of the phenomenon, our aim was to investigate its determinants among parents, with a specific view on those working as health professional. In 2017, parents of children aged 3-84 months were recruited online. Based on self-reported vaccine status and timeliness of vaccinations, parents were classified as pro-, hesitant, or anti-vaccine. The association between baseline characteristics and hesitancy was investigated with logistic regression adjusting for child's and parents' age, prematurity, presence of older children, previous vaccine adverse reaction in the child at issue, parents' nationality, education and employment status, health profession of at least one parent, single parenting, vegetarian lifestyle and perceived economic security. A total of 3, 865 questionnaires were collected (64% pro-, 32% hesitant, 4% anti-vaccine). Families with at least one health professional as parent were 20% of the sample. Vegetarian lifestyle (aOR 3.0; 95%CI 2.20-4.08), unsatisfactory (aOR 1.67 95%CI 1.08-2.58) and partially satisfactory perceived economic security (aOR 1.40; 95%CI 1.09-1.78) and previous vaccine adverse reactions (aOR 1.25; 95%CI 1.05-1.48) were associated with vaccine hesitancy, while having older children resulted as a protective factor (aOR 0.82; 95%CI 0.69-0.98). No significant association was found with other abovementioned variables, including parent employed as health professional (aOR 0.99; 95%CI 0.81-1.22). Vaccine hesitancy seems to be part of a lifestyle choice and, to a smaller extent, associated with previous vaccine adverse reactions and lower socioeconomic status. Interestingly, parents' level of education and employment in healthcare do not affect vaccine acceptance. The latter poses a challenge, given their crucial role in promoting vaccination. Key messages: Hesitancy is associated with lifestyle choices, experience of adverse reactions and socioeconomic status, while education and employment as health professional seem not to be relevant. Whether they are health professionals or not, parents' attitude towards their child's vaccinations is the same.